Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1190/1.1444517
|View full text |Cite
|
Sign up to set email alerts
|

Least‐squares migration of incomplete reflection data

Abstract: A least‐squares migration algorithm is presented that reduces the migration artifacts (i.e., recording footprint noise) arising from incomplete data. Instead of migrating data with the adjoint of the forward modeling operator, the normal equations are inverted by using a preconditioned linear conjugate gradient scheme that employs regularization. The modeling operator is constructed from an asymptotic acoustic integral equation, and its adjoint is the Kirchhoff migration operator. We tested the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
375
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 727 publications
(379 citation statements)
references
References 16 publications
(13 reference statements)
0
375
0
4
Order By: Relevance
“…The least-squares migration method (Lailly, 1984;Cole and Karrenbach, 1992;Schuster, 1993;Nemeth et al, 1999;Duquet et al, 2000) has been shown to sometimes produce migration images with better quality than those computed by conventional migration. When least-squares migration is implemented with the RTM method (Tang and Biondi, 2009;Dai and Schuster, 2010a;Dai et al, 2010;Wong et al, 2011;Dai et al, 2012), it can reduce not only the acquisition footprint but also the artifacts in the RTM image, while enhancing the image resolution.…”
Section: Chapter 2: Multisource Least-squares Reverse Time Migrationmentioning
confidence: 99%
See 4 more Smart Citations
“…The least-squares migration method (Lailly, 1984;Cole and Karrenbach, 1992;Schuster, 1993;Nemeth et al, 1999;Duquet et al, 2000) has been shown to sometimes produce migration images with better quality than those computed by conventional migration. When least-squares migration is implemented with the RTM method (Tang and Biondi, 2009;Dai and Schuster, 2010a;Dai et al, 2010;Wong et al, 2011;Dai et al, 2012), it can reduce not only the acquisition footprint but also the artifacts in the RTM image, while enhancing the image resolution.…”
Section: Chapter 2: Multisource Least-squares Reverse Time Migrationmentioning
confidence: 99%
“…Least-squares migration was originally implemented with Kirchhoff migration (KM) method (Nemeth et al, 1999;Duquet et al, 2000), but was later developed for phase shift migration algorithms (Kaplan et al, 2010;Huang and Schuster, 2012a). In this dissertation, I propose to implement LSM with reverse time migration (RTM) (Baysal et al, 1983;Whitmore, 1983;McMechan, 1983), where the Green's functions are calculated by finite-difference solution to the full wave equation instead of asymtotic Green's function in Kirchhoff migration (Bleistein, 1987), or one-way solution in one-way wave equation migration (Claerbout, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations